Study of the functional diagram and algorithm of tracking system for electrodynamic braking of DC electric train - V. A. Baranov; I. P. Vikulov; A. A. Kiselev; A. S. Maznev (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
One of the key ways to save operating costs in suburban traffic on lines electrified with direct current is to increase the return of electric energy when the drivers use the regenerative braking mode.Electrodynamic braking control systems that track the magnitude of the voltage of the contact network  can increase the percentage of return of electric energy from the use of regenerative braking due to the rapid redistribution of energy generated by traction motors. Similar systems (the so-called tracking systems) are used on DC electric trains with an asynchronous traction drive. In this work, authors analyzed an electrodynamic braking system for a DC electric train with a collector traction drive, which regulates the recovery current by changing the resistance of the braking resistor, and the armature current due to the magnetic flux of the motors. Characteristics of the pulse braking resistance controller for the current settings of the 250 and 350 A armature were calculated. Functional diagram of the tracking system with a description of its individual elements is developed. On a simulation model, electromagnetic processes in the  power circuit of an electric train were studied with a changing current consumption. Based on the analysis of the model results, the ability of the tracking system to regulate the armature current with full absorption of electricity by the consumer is shown. The article provides the refined algorithm for the transition of the servo system from the mode of regenerativerheostatic braking to rheostatic with excessive generation of electricity. The developed algorithm of the tracking system provides a stable implementation of the braking force in the entire range of speeds and at various levels of consumption of generated electricity. A rheostatic braking circuit with stabilization of the maximum value of the excitation current at low speeds is proposed.